MRI-powered biomedical devices. Issue 4 (4th July 2018) - Hovet, Sierra; Ren, Hongliang; Xu, Sheng; Wood, Bradford; Tokuda, Junichi; Tse, Zion Tsz Ho
Abstract: Magnetic resonance imaging (MRI) is beneficial for imaging-guided procedures because it provides higher resolution images and better soft tissue contrast than computed tomography (CT), ultrasound, and X-ray. MRI can be used to streamline diagnostics and treatment because it does not require patients to be repositioned between scans of different areas of the body. It is even possible to use MRI to visualize, power, and control medical devices inside the human body to access remote locations and perform minimally invasive procedures. Therefore, MR conditional medical devices have the potential to improve a wide variety of medical procedures; this potential is explored in terms of practical considerations pertaining to clinical applications and the MRI environment. Recent advancements in this field are introduced with a review of clinically relevant research in the areas of interventional tools, endovascular microbots, and closed-loop controlled MRI robots. Challenges related to technology and clinical feasibility are discussed, including MRI based propulsion and control, navigation of medical devices through the human body, clinical adoptability, and regulatory issues. The development of MRI-powered medical devices is an emerging field, but the potential clinical impact of these devices is promising.